EVALUATING EFFECTIVENESS OF NEW METHOD OF LAPAROSCOPIC TREATMENT OF INCARCERATED INGUINAL AND INGUINAL-SCROTAL HERNIAS IN CHILDREN - Azat M. Mukhametzyanov; Vladimir G. Alyangin; Robert N. Akbashev; Adik A. Salimgareev (Креативная хирургия и онкология)
Introduction. Congenital inguinal hernia is a common pediatric surgical disease. It is traditionally treated by open herniotomy with high ligation of the hernia sac. To date despite the technical capabilities the incarcerated inguinal and inguinal-scrotal hernias are a contraindication to laparoscopic surgery, and in the available literature there is no information about using endovideolaparoscopic method to treat this pathology in children. In this context, the main objective of this work is to develop a method of laparoscopic treatment of incarcerated inguinal and inguinal-scrotal hernias in children. Materials and methods. The paper presents the results of the diagnosis and laparoscopic treatment of 23 children aged 1 month to 3 years, with incarcerated inguinal and inguinal-scrotal hernias, that has been carried out at the clinic of Pediatric Surgery of BSMU based at City Children Clinical Hospital №17 in UFA in the period 2002-2016  with original method of endovideosurgical dis-incarceration with simultaneous plasty of hernia orifice. Results. According to the results of the analysis the average operation time was 25±4.2 min. The method facilitated early activation and early enteral meal. There were no local complications in aftercare period by trocar wounds, the stitches were removed on the 5th day. The average duration of hospitalization was 6 days. Long-term results through 3 and 6 months have demonstrated the absence of any asymmetry of the groin, tightness of the testicle, increased or reduced testicle volume. Conclusion. Thus, the findings show that laparoscopic hernioplasty for inguinal and inguinal-scrotal hernia, is a new technique and it gives opportunity to solve this problem in children at a whole new level.